Family Versus Individual Therapy: Impact On Discrepancies Between Parents' And Adolescents' Perceptions Over Time. (8th May 2012) - Guo, Xiamei; Slesnick, Natasha
<x xml:space="preserve">Abstract</x> This study examined the degree of disagreement between runaway adolescents and their primary caretakers, defined as informant discrepancies, on their view of their family. How these discrepancies changed over time and whether family therapy or individual therapy could impact that change were also explored. The current sample (N = 179 dyads) included adolescent substance abusers residing in a runaway shelter and their primary caretakers. Adolescent gender was examined as a correlate of change, and treatment attendance was controlled. The intraclass correlation coefficient was used to measure discrepancies between the individuals within a dyad. Results showed that among those receiving family therapy, but not individual therapy, informant discrepancies decreased significantly over time. Additionally, dyads with a male adolescent showed a significantly slower rate of improvement in discrepancy scores across time compared with dyads with a female adolescent. Previous research indicates that lower levels of discrepant perceptions are associated with better individual and relationship functioning. Therefore, this study's findings support family therapy as superior to individual therapy for addressing parent–child discrepancies––possibly through its focus on improving family communication, perspective taking, and understanding.